Bridging the science and policy divide to enable livestock adaptation and mitigation solutions - International Livestock Research Institute (International Livestock Research Institute, 2022)
Bernard Kimoro leads the climate change and livestock sustainability work of Kenya’s Ministry of Agriculture and Livestock. In this video Bernard speaks of the challenges livestock production is facing because of climate change impacts. He refers to the transboundary nature of these challenges and the need for large-scale initiatives to address them. He highlights the important role that research is playing in helping countries like Kenya develop evidence-based policies to facilitate and scale out climate adaptation initiatives.